Implementasi Fatwa Dsn-Mui No: 107/Dsn-Mui/X/2016 Tentang Pedoman Penyelenggaraan Rumah Sakit Berdasarkan Prinsip Syariah Di Rumah Sakit Qolbu Insan Mulia Batang - Assilmi Kaffatan Ats Tsaury; Siti Qomariyah (el hisbah: Journal of Islamic Economic Law, 2022)
DSN MUI Fatwa No. 107/DSN-MUI/X/2016 on October 1, 2016 has stipulated the provisions that must be met by every Hospital that uses a Sharia-based system. So there is a difference between the General Hospital (RSU) and the Sharia Hospital. Recently, many hospitals have implemented sharia principles, especially in terms of their services, one of which is the Qolbu Insan Mulia Batang General Hospital. Therefore, this study aims to analyze and describe the implementation of DSN-MUI Fatwa No: 107/DSN-MUI/X/2016 at RSU Qolbu Insan Mulia Batang whether the service aspect is in accordance with DSN-MUI Fatwa No: 107/DSN- MUI/X/2016. This type of research is field research (field research) using a qualitative approach. Analysis of the data using descriptive qualitative. Based on the results of the study it can be seen that the management system of RSU Qolbu Insan Mulia Batang in implementing sharia principles which includes contracts, services, medicines, food and beverages and management of funds is not fully in accordance with the DSN-MUI fatwa No. 107/DSN-MUI/X//2016.